â€˜Local Wisdomâ€™ and Law - Stefan Koos (Sociological Jurisprudence Journal, 2024)
Bali, as a province with strong roots in local cultural traditions and significant economic importance for Indonesia, is striving to balance modernity and tradition, economics, especially mass tourism, and cultural identity. This is why Universitas Warmadewa, one of the largest Balinese universities, chooses the theme â€˜Local Wisdom and Business Lawâ€™ for its international conferences each year.As a non-Indonesian legal scholar, this theme presents two challenges for me. Firstly, I am not an expert in tourism economics and can only approach the topic from a traditional market law perspective, theoretically. Secondly, the terms used in Indonesian legal discussions may seem vague and unclear from a German perspective, as the legal discussion in Indonesia integrates traditional legal phenomena pragmatically into the applicable legal system. This may also be historically conditioned because since independence Indonesia has to handle a legal pluralism in law, which also finds its cause in the legacy of the colonial era.When speaking on the legal perspective of â€˜local wisdomâ€™, several questions are unclear to me:What exactly is local wisdom and how can it be defined?Where does it fit into the Indonesian legal system?What role can local wisdom play in contemporary law?Local wisdom may be understood as part of traditional customary law or Adat, at least in terms of its influence on legal issues, as the conference theme suggests. The terminology around â€˜customary lawâ€™, â€˜Adatâ€™, â€˜indigenous lawâ€™, or â€˜living lawâ€™ is still a problematic issue in Indonesian scientific discussion and should only be briefly mentioned in this presentation. The term â€˜Adat lawâ€™ was originally not used in Indonesian society and was first systematically used by the Dutch. Van Vollenhoven, considered the â€˜father of Indonesian Adat lawâ€™ by Indonesian scholars, defined Adat law as law that is not based on codified legal rules from the legislator. This definition is still used by contemporary Indonesian scholars. Adat law in this sense contains sanctions, making the character of â€˜lawâ€™. It was characterized by Van Vollenhoven as dynamic and flexible folk law, which combines the term with the often-used term of â€˜living lawâ€™. There are numerous discussions in Indonesian literature about Indonesian customary law, its functions, and significance, but the terminology has not been clearly defined and the role of religious law is also subject to numerous publications.Therefore, having read various contributions on the topic, I am left confused because some of them discuss the existence of legal principles of living customary law and describe them as â€œnational Indonesian principles,â€ which can replace parts of the post-colonial Indonesian law, but they do not clearly identify these principles. The topic seems to be of almost patriotic importance to Indonesia, making it particularly difficult for foreign scholars to approach the subject in presentations before Indonesian colleagues. My contribution should be seen in light of this difficulty, as a first observation of the phenomenon from a foreign perspective.The term Adat is already difficult to comprehend, and this is even more true for the term â€œlocal wisdomâ€ in a legal context. So, what is the â€œLocal Wisdomâ€ that I am asked to talk about? The Terms of Reference of our conference describe the meaning of â€œlocal wisdomâ€ mainly as the clash of market actors in local Balinese tourism that can lead to conflicts, which the law should resolve. These conflicts are said to occur because local communities and institutions, based on a kind of traditionally grown trust, seek to build and maintain their business relationships in the tourism industry. This trust, which one could call â€œtraditional good faith,â€ meets the need to regulate contractual arrangements more formally in terms of contract law (â€œmore official...instead of just relying on promises or good faithâ€).In this sense, local wisdom is an aspect of good faith. Based on this understanding of the term, I have no systematic issues with the term â€œlocal wisdom.â€ However, it should be noted that good faith and contract, as a predictable shaping of legal relationships between market actors, should not be seen as opposites. It is possible and necessary to resolve disruptions in contractual relationships in light of good faith and, if necessary, adapt contractual regulations. Here, â€œlocal wisdomâ€ should not be understood as a unique source of good faith, but as a general aspect that can influence the expectations of the contracting parties and their trust in shaping the law. This raises the question of which factors should be taken into account by the non-local contracting party in good faith, and which should not. It is a question of the concrete assessment of the structure of interests and the balance of the contract, how to allocate risk and assign external aspects to the contracting parties and which aspects should be considered subsequently.This is a theoretical matter, and it is unlikely to play a significant role in practice since local market actors and communities have the freedom, within the framework of private autonomy, to incorporate their traditional interests into the contract negotiations. This allows for traditional interests to participate in the â€œequivalence justiceâ€ of the contract. However, if the traditional interests of the local community result in unacceptable consequences for the contractâ€™s execution, the question of whether these reasons can lead to a change in the contractâ€™s basis may arise. In civil law systems, the clausula rebus sic stantibus is regulated as a limitation of the pacta sunt servanda principle and falls under the principle of good faith (bona fides). If the invocation of â€œlocal wisdomâ€ by one party leads to the other party having to agree to an adjustment, it would have to be examined.I would like to give you an example of this, which seems credible even if no prove about the issue can be delivered due to the â€˜popularâ€™ source: A person without Indonesian citizenship acquired the right to use a plot of land with a house in Bali ten years ago. Since foreigners cannot acquire land ownership in Indonesia themselves, the foreigner had agreed on a legal arrangement with an Indonesian citizen resident in Bali, in which the Indonesian acquired ownership (hak milik) of the land with the foreignerâ€™s money and agreed on right to use for the foreign partner. After ten years, the foreigner wanted to sell the property again to move to his country of origin. The agreement with the Indonesian partner stipulated that the Indonesian partner must agree to the sale of the plot on the wish of the foreign partner and would receive 10% of the sale amount in the event of a sale. In the case described, however, the Indonesian partner seems to have refused to sell the property on the agreed terms. He was not satisfied with the 10% share and demanded a 70% share instead. As justification for this, he argued that the contract terms should be changed because he had spiritually enhanced the property over the years through certain religious rituals and this required a revaluation of his shareholding.It is not known whether the case was heard in an Indonesian court and how it was finally settled. Assuming the case had occurred as described, from the perspective of Indonesian civil law, it is clear that no change in the business basis of the contract occurred as a result of the Indonesian partnerâ€™s spiritual acts, which can lead to an adjustment of the agreement between him and the foreign contractual partner. Just as local communities depend on their interests in cultural identity being taken into account even in legal relations with partners coming from outside, foreign investors must be able to rely on certain standards of contractual obligation. The principle of good faith would be grotesquely overstretched if local contracting partners could use fuzzy notions of â€˜local wisdomâ€™ to make contractual arrangements more flexible in their favour.Another example of the clash between traditional legal customs and supra-regional legal ideas in highly traditional markets with supra-regional economic importance, such as Bali, is the handling of legal disputes and methods of dispute resolution. The trust of traditional communities in supra-legal ties of interest in business relationships, as mentioned in the Terms of Reference to this Conference, meets a systemic trust in formal contractual regulations of non-local actors. The reference points of trust of the respective groups of market actors thus differ. This also affects dispute resolution. According to Sulastriyono, the voluntary character of traditional customary law has the advantage over civil law methods of litigation and dispute resolution of a â€˜win-winâ€™ solution, which leads to greater acceptance of the solution by the parties to the conflict. In theory, this is undeniable. However, it is questionable whether this acceptance can also be achieved among contract participants who do not originate from the respective culture, because the existence of sufficient advantages for a party may well depend on the integration of the party in the respective local society. Moreover, the indisputable advantages of consensual dispute resolution can also be well integrated in state procedural law via mediation mechanisms.Cases such as the one outlined one above would in principle be likely to erode the confidence of foreign investors in Indonesian law in general if courts do not rule clearly and draw clear boundaries here. The example seems to be a particularly extreme case, but it shows how important it is to clearly determine the meaning and possible role of terms such as â€˜local wisdomâ€™ and â€˜traditionâ€™ for use in law. Culturally related aspects are prone to serve as a tool for discrimination against individuals and companies that do not belong to the respective cultural environment. The difficulty, for example, of establishing an intellectual property right on cultural heritage follows not only from the contrast between individual subjective rights and collective subjective rights. It follows above all from the problem of determining the collective rights holders who are to benefit from â€˜theirâ€™ cultural heritage. Who is a member of a certain culture? Is there a generational link or does it depend on the integration of the individual into his or her living environment? If the legal system does not want to fall back to abstruse considerations of â€˜blood identityâ€™, what remains is the assignment of such claims to territorial authorities or the state itself, whose task it is to protect cultural diversity on its territory. This is the path that the Indonesian legislature had taken in Art 38 Law No 28/2014 on copyright law.The misuse of cultural aspects carried into the application of law is also visible in another aspect: In another paper I have pointed out the problem that the concept of traditional customary law in Indonesian law and the position of Adat law in the hierarchy of norms seems in need of clarification. Shidarta notes that there is no sufficient clarity about the relationship between Adat law and state law and thus no consistent system of Indonesian law as a whole. Accordingly, the maturation of an independent Indonesian legal system suffers to this day from the internal conflict with the colonial legacy of existing state law based on Dutch civil law and the lack of a consistent overarching pluralistic concept of law. This is seen by Shidarta as a major reason why the systematic positions of customary law, Islamic law and western law within national law are not clearly defined and why a clear hierarchical determination of the various sources of law in relation to national law is lacking. The doubts about the systematic location and certainly also the failure to establish the principles of traditional customary law as original Indonesian law after the attainment of independence instead of the sources of law inherited from the colonial period are probably due - in addition to the idea of the state founders of an Indonesian unitary state (â€˜eenheidstaatâ€™) - above all to the disagreement about the concept of customary law, which is formally understood in the sense of a binding source of law defined during the colonial period, or as post-colonial Adat law in the sense of traditional customary rights of various Indonesian ethnic groups either with a binding character or as norms of social order based on voluntariness. In this respect, too, different definitions of the term can be found in the literature:There is thus generally a more philosophical recognition of the importance of traditional customary law in the sense that customary law reflects the actual sense of law of the people and the Indonesian people as a nation. The latter statement seems problematic to me because the statement only applies with regard to the significance of customary law as a source of law, but not to the content of the individual customary laws of the various ethnic groups, in which different legal customs apply in each case. It therefore seems questionable to me whether Adat law can be understood in the sense of an alternative to Indonesian state law. In my opinion, Adat as a source of concrete legal norms has a supplementary development perspective in the communal area. Here it can certainly have an influence on economic life in the regions if it is applied consistently and transparently, and its importance would grow especially if the autonomy of municipal territorial units were strengthened, and a strong federalism were developed. However, a scientific inventory of norms and principles of local customary law is then required, and a clear formulation of such norms is needed, because it must be ruled out that the invocation of undefined, non-transparent or arbitrarily formulated Adat rules unduly restricts the freedom of market actors and are used as protectionist instruments in the provinces.In this sense, I believe that the postulate that Indonesian law must simply recognise Adat law as it has grown and as it is applied alive within the Indonesian local societies falls short, because the compatibility of social rules based on voluntariness and constantly changing with the overall legal system based on the rule of law is at least debatable. In other words: either one renounces the legal certainty and predictability of legal norms in the area of traditional customary law. This could then constitute a breach of the constitutionally enshrined principle of the Rule of Law. Or one formulates clear norms based on traditional legal principles, which have the character of binding legal norms and applies them in the sense of subsidiarity in the local environment with priority over central state law in certain predefined aspects. Then the rules of the hierarchy of norms must be correspondingly clear. However, the question of the hierarchy of norms then no longer presents itself as a problem of the nature of Adat or customary law because the latter would have lost its character as actual customary law. The advocates of a strong recognition of Adat by state law will, however, reject this path because they see the advantage of traditional customary law over state law precisely in its flexibility and ability to change. This flexibility would no longer be readily available through an integration of traditional principles into a local classical law in the sense of imperative norms.A clear hierarchy of norms defined by constitutional law seems indispensable, because such local customary law cannot displace state law without further ado, but only if the principle of subsidiarity and the better regulation of local circumstances by local law indicates otherwise. This would also be in line with the philosophical assessment of local customary law as the law that best captures the living conditions of the people in its cultural area of application. The importance of the principle of subsidiarity should generally be given more attention in the discussion on legal pluralism in Indonesia. This can not only ensure greater recognition of traditional customary law, but also enable the transparency necessary for the predictability of the law.Insofar as Adat is to be understood as the source of â€˜abstract normativeâ€™ aspects, as certain common Indonesian legal values and principles in the sense of a â€˜pan-Indonesianâ€™ legal order and, as such, is to find its way into an independent state Indonesian civil law, legal scholarship in Indonesia will also have to identify and clearly define these principles. In doing so, it will be necessary to determine which principles of traditional customary law in the various regions of the archipelago are suitable as overarching legal principles, so that they can possibly have an identity-forming effect in a national private law. This difficult process might lead to reform of the Indonesian Civil Law which meets the special requirements of a socially and culturally integrated legal system.Indonesia as a state with a unified internal market needs a cross-cultural private law and commercial law. Consideration of the interests of local communities and traditions is of importance in a multicultural state. The Indonesian constitution therefore emphasises the specifics of traditional rights and thus guarantees Adat its own status in the legal system. However, there seems to be a lack of a clear hierarchy of norms in the legal system and a clear definition of the nature of Adat. A hint of a certain hierarchy between Adat and state law is indeed found in agricultural law (Art. 5 Law No. 5/1960 on the Basic Regulations of Agrarian Principles) and in forestry law (Law No. 41/1999 on Forestry). Adat is recognised here but must harmonise with state law. It is therefore likely to be in a relationship of subsidiarity to state law. The fundamental assertion of the primacy of state law over other co-existing legal systems is also in line with the view of Indonesian legal scholars such as Sunaryati Hartono. Referring to Griffithsâ€™ formulation of â€œweak legal pluralismâ€, where co-existing legal systems are subordinated to a dominant formalistic national law, it can be stated that the Indonesian legal system follows this model.In my opinion, the integration of traditional customary law into the legal system should not be done as a mere tolerance of state law towards deviating regulations of facts in certain regions. From my perspective as a foreign observer, this seems to lead to significant problems for the development of the Indonesian economy and for investment. In particular, this seems to me to be the case for Bali. Local Wisdom can be incorporated into the contractual relations of the parties within the framework of private autonomous arrangements. A â€˜creativeâ€™ qualification of protectionist measures against outside market actors or the justification of the failure to sanction breaches of contract or violations of law against outsiders as â€˜Adatâ€™ or â€˜protection of local traditionsâ€™ should be consistently avoided.Incidentally, it seems to me that in contract law there is no real opposition between state law and traditional customary law. Either the parties trust each other, in which case state law does not prevent an agreement based on good faith. Or they do not, in which case only state contract law can lead to proper solutions. The same applies to traditional dispute resolution methods, to which the parties to the conflict can easily submit. In contrast, the integration of customary law as independent Indonesian legal principles or as legal norms at the local or municipal level into Indonesian law would require considerable academic effort. For this, the principles concerned would have to be clearly identified, systematised, and formulated to be able to substantiate a claim to validity beyond the respective local communities. The mere reference to historically evolved convictions of local communities is too vague. The term â€˜local wisdomâ€™ seems to me to be problematic in this sense to accurately describe the question of the collision of traditional customs and expectations of outside market actors, especially since it is already conceptually positively evaluative. Finally, it should not be forgotten, that the continental European codifications are culturally neutral and in big parts based on the Roman law. Roman law itself was not developed under the cultural framework of northern and middle European regions, however it served well as source for the modern European codifications. These codifications are working fine until these days in different nations without obvious incompatibilities with local traditions. The amount of a â€˜Volksgeistâ€™ after the idea of Friedrich Carl von Savigny within the Private Law does not play a big role in the contemporary discussion as law should be seen in a pragmatic way as a viable tool to organize the modern society. Indonesia is an important economically emerging nation. As such it might be a good idea to keep an internationally compatible private law, which might be carefully adapted to certain peculiarities of the Indonesian society. The use of general clauses as entrance doors for local legal convictions seems to be a good way for that and a clearly defined legal hierarchy with a constitutionally based legal subsidiarity principle seems important. In contrast, the foundation of modern law on nationalistic, local, or indigenous traditional customs should only be done with extreme caution, if at all. The contemporary discussion on the role of Adat in Indonesian law shows the great difficulty of determining viable legal rules that can enter a future reformed Indonesian private law as â€˜originally Indonesianâ€™. The criticism against Von Savignyâ€™s â€˜Volksgeistâ€™ idea also applies here: Defining who the â€˜peopleâ€™ are and what constitutes their common identity is already hardly rationally possible in a non-multi-ethnic state, even more in a multi-ethnic state. National identity-forming circumstances are hardly suitable as common principles for pluralistic societies.